Current source inverter for PV application - Tang, Kennett Kang You (Nanyang Technological University, 2024)
With the growing emphasis on renewable energy due to the harmful effects finite resource of fossil fuels, the integration with photovoltaic (PV) systems with power electronics have emerged as a promising solution for the clean energy generation and plays a crucial role in maintaining maximum energy extraction. PV systems are renewable, abundant and healthy for the environment which can solve the problem on having a better a better earth for everyone. In this project PV system will be using the current source inverter to convert DC to AC current using 3 different control methods, Sine Pulse Width Modulation (SPWM), Space Vector Pulse Width Modulation (SVPWM) and Model Predictive Control (MPC) to get the least Total Harmonic Distortion (THD). The software used in this project is MATLAB.